PENERAPAN WEBSITE SISTEM INFORMASI MANAJEMEN NIKAH SEBAGAI APLIKASI PENDAFTARAN NIKAH SECARA ONLINE DI KUA KECAMATAN MLONGGO - Khabib , Muhammad (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
SIMKAH web is an application for conducting marriage administration activities at the District KUA, such as at the Mlonggo District KUA. According to the Head of the Mlonggo District KUA, many people still do not understand how to use the SIMKAH Web service. The research objectives to be obtained are: (1) The application in the application of SIMKAH at the Mlonggo District KUA regarding marriage registration; (2) whether it is in accordance with the mandate of PMARI No. 20/2019 concerning Marriage Registration; (3) Viewed from the perspective of maslahah as-syatibi. This article is a descriptive qualitative type of field research, normative-empirical approach. Interview and documentation approaches are used to obtain data. The following are the results of this research: First, the KUA of Mlonggo District in terms of marriage administration has implemented SIMKAH well and has conducted socialization to the community and also provided assistance services; Second, the implementation of SIMKAH at the KUA of Mlonggo District, especially regarding marriage registration, follows PMA Number 20 of 2019; Third, marriage registration through SIMKAH is in accordance with maslahah as-syatibi in terms of hajjiyah to dhoruriyyat.